Project-based learning improves outcomes in english for islamic banking and accounting - Welly Kuswanto; Farqan Balqia (Indonesia Auditing Research Journal, 2025)
The gap between the demands for professional English language competence in the Islamic Finance sector and the achievements of students of English for Islamic Banking and Accounting (EfIBA) within the framework of Outcome-Based Education (OBE) is not yet optimal. The main objective of this study is to analyze the effectiveness of the Project-Based Learning (PBL) model in improving these outcomes. The method used was quantitative with a non-equivalent control group quasi-experimental design. The sample included a total of 70 EfIBA students, divided into an experimental group (PBL) and a control group (conventional). The main instrument was an authentic project performance test assessment rubric. Data analysis used an independent T-test. The main results showed a very significant difference (p ≤ 0.001) in the outcome achievement scores between the two groups, with the average score of the PBL group (85.90) substantially higher than that of the control group (76.55). The research conclusion indicates that PBL is a superior learning strategy because it successfully integrates Sharia knowledge and English language skills in practice. Implicitly, this model is recommended for dual-specialization courses to ensure the relevance of OBE-based graduates to modern professional needs.